Female Cat Intravesical Sequestration after Ovariosalpingohisterectomy Using Nylon Clamp - Andrade, Larissa Caroline Cordeiro de; Amaral, Andréia Vitor Couto do; Carvalho, Camila Franco; Bonfim, Leuton Scharles; Rosa, Igor Ribeiro; Saturnino, Klaus Casaro (Acta Scientiae Veterinariae, 2020)
Background: The nylon clamp, marketed as an accessory of electrical devices, has been used as an alternative method for definitive surgical hemostasis by ligature of arteriovenous vessels in ovariosalpingohisterectomy (OSH) in bitches and female cats. However, since May 2015, the Brazilian Veterinary Statutory Body (CFMV - Conselho Federal de Medicina Veterinária) banned its application, once it is a material still not regulated to be used in animals, in addition to the numerous reports of postoperative complications. This paper reports the migration of the clamp used in the OSH to the urinary bladder of the cat and the implications of the presence of the foreign body, in addition to discussing the use of this device in surgeries. Case: A 1-year-old Persian female cat, which, three months after an elective OSH in a private veterinary clinic, presented polyuria and hematuria. The patient presented pain at abdominal palpation; in the WBC were observed leucopenia and eosinophilia, indicating a chronic inflammatory process installed; the urinalysis showed the presence of crystals, increased urinary density, milky aspect indicating presence of pus, proteinuria and hematuria; on ultrasound were observed the presence of two amorphous mobile structures inside the bladder, producing acoustic shadow, measuring approximately 0.4 and 0.6 cm in diameter, suggesting the presence of bladder urolithiasis. Considering the results, the patient was sent for a cystotomy. The association of acepromazine (0.02 mg/kg), midazolam (0.2 mg/kg), morphine (0.2 mg/kg) and ketamine (10 mg/kg) was used intramuscularly as preanesthetic medication. For anesthetic induction, 5 mg/kg of propofol was applied intravenously, in addition to epidural anesthesia with 1 mL/4 kg of lidocaine along 0.1 mg/kg of morphine and, for maintenance, isoflurane in oxygen at 100% was used. Then, a four-centimeter retro-umbilical incision was performed to exhibit the bladder. After the incision on the ventral aspect of the bladder wall, a nylon clamp with approximately 0.8 cm, present in the lumen was found and removed. The seromuscular synthesis of the bladder was with a 3-0 mononylon simple continuous suture, the muscle with a 2-0 mononylon sultan pattern, and in the skin an interrupted simple suture using 2-0 nylon was performed. Postoperative care comprised by amoxicillin with potassium clavulanate (15 mg/kg, orally, 8/8 h, 7 d), meloxican (0.15 mg/kg, orally, 24/24 h, 4 d) and tramadol (12 mg/kg, orally, 12/12 h, 4 d). After ten days, surgical stitches were removed, with good healing and clinical improvement, as well as remission of the symptomatology reported on anamnesis and physical examination. Discussion: The pathophysiology of the nylon clip migration probably occurred in a similar way to the intravesical migration of intrauterine devices (IUDs) to the abdominal cavity, bladder and intestine, in women. According to reports, it is a progressive event, in which several factors may be involved, mainly: inadequate implantation of devices, uterine infections, use of contaminated medical instruments, among others, followed by an inflammatory process, perforation of the uterine wall by the device, adhesions and migration to adjacent structures. In the present report, it is believed that the clamp lock failed in the procedure performed by the veterinarian responsible for OSH, with subsequent loosening and detachment, and migration to the urinary bladder, an organ located ventrally to the uterine body. However, the following hypotheses can also be raised: pregnancy at the moment of castration, followed by uterine stump retraction and release of the clamp; contamination of surgical instruments; postoperative infections and adhesions involving the bladder.